2010
DOI: 10.1038/jcbfm.2009.254
|View full text |Cite
|
Sign up to set email alerts
|

Functional Brain Abnormalities Localized in 55 Chronic Tinnitus Patients: Fusion of SPECT Coincidence Imaging and MRI

Abstract: Tinnitus is often defined as the perception of sounds or noise in the absence of any external auditory stimuli. The pathophysiology of subjective idiopathic tinnitus remains unclear. The aim of this study was to investigate the functional brain activities and possible involved cerebral areas in subjective idiopathic tinnitus patients by means of single photon emission computerized tomography (SPECT) coincidence imaging, which was fused with magnetic resonance imaging (MRI). In this cross-sectional study, 56 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 30 publications
1
36
2
1
Order By: Relevance
“…Husain et al pointed out that the perception of chronic tinnitus may place the subject in a task state rather than a "true resting-state" (Husain and Schmidt, 2014). However, previous studies based on SPECT (single photon emission computerized tomography) and EEG (electroencephalogram) showed increased activity in the PCC areas in chronic tinnitus patients (De Ridder et al, 2011;Farhadi et al, 2010). This may be due to the function of PCC: it mediates the processes of episodic memory (Greicius et al, 2004) and sensorimotor, as well as spatial and attentional processes (Sorg et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Husain et al pointed out that the perception of chronic tinnitus may place the subject in a task state rather than a "true resting-state" (Husain and Schmidt, 2014). However, previous studies based on SPECT (single photon emission computerized tomography) and EEG (electroencephalogram) showed increased activity in the PCC areas in chronic tinnitus patients (De Ridder et al, 2011;Farhadi et al, 2010). This may be due to the function of PCC: it mediates the processes of episodic memory (Greicius et al, 2004) and sensorimotor, as well as spatial and attentional processes (Sorg et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Neuroimaging, especially the resting-state functional MRI (rs-fMRI) technique, has proven to be a useful tool for studying the neural activity in patients with tinnitus (Burton et al, 2012;Chen et al, 2014;Engineer et al, 2011;Farhadi et al, 2010;Han et al, 2014;Lanting et al, 2009;Maudoux et al, 2012aMaudoux et al, , 2012bSaunders, 2007;Schecklmann et al, 2013;van der Loo et al, 2009;Vanneste et al, 2011aVanneste et al, , 2011bVanneste et al, , 2011c. However, the PT patients were excluded in these studies due to the involvement of completely different mechanisms of these two subtypes of tinnitus Husain and Schmidt, 2014;Lanting et al, 2009;Li et al, 2013;Moller, 2007;Schecklmann et al, 2013;Shi et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Several functional imaging studies [17][18][19][20] have shown that individuals who experience tinnitus have increased activity in the auditory cortex compared with control subjects, even in the absence of external auditory stimuli. Other studies [21][22][23] demonstrated that nonauditory brain regions might also contribute to the perception or severity of tinnitus.…”
Section: Mechanisms Of Tinnitusmentioning
confidence: 99%
“…Considerable effort has been directed at the identification of aberrant neural activity within the classical auditory pathway that could give rise to the phantom sound of tinnitus and hyperacusis. Human brain imaging studies have identified abnormal neural activity in many different structures within the auditory pathway of patients with tinnitus and hyperacusis, but aberrant activity has also been found outside the auditory pathway (Andersson et al, 2000; Arnold et al, 1996; Farhadi et al, 2010; Giraud et al, 1999; Langguth et al, 2006; Lockwood et al, 1998; Mirz et al, 1999; Mirz et al, 2000a; Reyes et al, 2002; Shulman et al, 1995). …”
Section: Introductionmentioning
confidence: 99%